Identifikasi Serkaria Fasciolopsis buski dengan PCR untuk Konfirmasi Hospes Perantara di Kabupaten Hulu Sungai Utara, Kalimantan Selatan, Indonesia - Budi Hairani; Annida Annida; Syarif Hidayat; Deni Fakhrizal (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Fasciolopsiasis in Indonesia is endemic in Hulu Sungai Utara District, South Kalimantan. Problems in controlling this disease is to identify the snail that acts as an first intermediate host. Fasciolopsis buski intermediate host is determined by the presence of F. buski cercariae on the conch. Identification of cercariae using microscopic method can not ensure that was F. buski cercariae, so it is necessary to use a more accurate method. Therefore, the research aimed to identify F. buski cercariae using Polymerase Chain Reaction ( PCR ) to confirm the cercariae species and the first intermediate host snails of F. buski. Observational studies in the field and laboratory are conducted in March -December 2014. Snail samplings were taken place at Sungai Papuyu and Kalumpang Dalam villages. Cercariae PCR analys is was done at Molecular Biology Laboratory, Faculty of Science-Lambung Mangkurat University, Banjarbaru. Our field collections found 6 snail genus: Pomacea, Bellamya, Indoplanorbis, Lymnaea, Gyraulus, and Melanoides. Three species of cercariae obtained by microscopic examination consisted of Echinostome cercariae in Lymnaea and Indoplanorbissnail, Brevifurcate-pharyngeate cercariae in Lymnaea snail, and Sulcatomicrocercous cercariae in Bellamya snail. PCR analysis showed positive result of F. buski on Echinostome cercariae samples found from Lymnaea and Indoplanorbis snail. This finding have confirmed that both snails were the first intermediate host of F. buski at our sampling sites.